Are medium‐scale farms driving agricultural transformation in sub‐Saharan Africa? - Jayne, Thomas S.; Muyanga, Milu; Wineman, Ayala; Ghebru, Hosaena; Stevens, Caleb (Blackwell Publishers, 2019)
This study presents evidence of profound farm‐level transformation in parts of sub‐Saharan Africa, identifies major sources of dynamism in the sector, and proposes an updated typology of farms that reflects the evolving nature of African agriculture. Repeat waves of national survey data are used to examine changes in crop production and marketed output by farm size. Between the first and most recent surveys (generally covering 6 to 10 years), the share of national marketed crop output value accounted for by medium‐scale farms rose in Zambia from 23% to 42%, in Tanzania from 17% to 36%, and in Nigeria from 7% to 18%. The share of land under medium‐scale farms is not rising in densely populated countries such as Kenya, Uganda, and Rwanda, where land scarcity is impeding the pace of medium‐scale farm acquisitions. Medium‐scale farmers are a diverse group, reflecting distinct entry pathways into agriculture, encouraged by the rapid development of land rental, purchase, and long‐term lease markets. The rise of medium‐scale farms is affecting the region in diverse ways that are difficult to generalize. Findings indicate that these farms can be a dynamic driver of agricultural transformation but this does not reduce the importance of maintaining a clear commitment to supporting smallholder farms. Strengthening land tenure security of local rural people to maintain land rights and support productivity investments by smallholder households remains crucial.